Iso-radioactivity curves of the water of the Hazar Lake, Elazig, Turkey - Dogru, M; Külahci, F (Springer, 2004)
Alpha and beta radioactivity concentrations have been determined in the Hazar Lake (East of Turkey) surface, middle and bottom water. The total alpha-radioactivity concentration in the surface, middle and bottom levels varies from 0.32 to 2.52 Bq/l, from 0.21 to 2.70 Bq/l and from 0.12 to 0.96 Bq/l, respectively. The beta-radioactivity concentration in the surface, middle and bottom water levels varies from 0.01 to 0.16 Bq/l, from 0.01 to 0.27 Bq/l and from 0.03 to 0.23 Bq/l, respectively. The iso-radioactivity curves were drawn from the obtained data during 1998-2001.